The influence of training in supply chain management on competitiveness / Arawati Agus, Za'faran Hassan and Zulridah Mohd. Noor - Agus, Arawati; Hassan, Za'faran; Mohd. Noor, Zulridah (Institute of Business Excellence, 2010)
This paper examines the relationship between training in supply chain management (SCM) and competitive advantage of manufacturing companies in Malaysia. The study measures senior SCM managers’ or production managers’ perception of training in SCM practices and level of competitiveness in the industry. Associations between training in supply chain management and competitive advantage are analyzed through methods such as Pearson’s correlations, cluster analysis and structural equation modelling (SEM) utilizing 115 respondents’ data. The findings suggest that training in SCM has significant correlations with competitive advantage (comprises of determinants such as product differentiation, employee differentiation, service differentiation and price differentiation). Specifically, competitive advantage (CA) has high correlations with training variables such as ‘adequacy of production training among employees’, ‘management training in supply chain effectiveness’ and ‘employee training in supply chain technologies’. The SEM result also reveals that training in SCM exhibit direct impact on competitiveness. Findings of the study provide a demonstration of the importance of training in enhancing competitiveness in Malaysian manufacturing companies.